Enveloping Lie Superalgebras and Killing-Ricci Forms of Bol Superalgebras - Sylvain Attan (Journal of Mathematics)
In this paper, enveloping Lie superalgebras of Bol superalgebras is introduced. The notion of Killing-Ricci forms and invariant forms of these superalgebras is investigated as generalization of the one of Bol algebras.